Analisis pemasaran rumput laut (Eucheuma denticulatum) di Desa Napa Kecamatan Mawasangka Kabupaten Buton Tengah - Setiawan, Jodi; Budiyanto; Yusuf, Sarini; Siang, Roslindah Daeng; Risfandi; Ruslaini (Universitas Halu Oleo, 2024)
This study aims to determine the effectiveness of seaweed (Eucheuheuma denticulatum) marketing in Napa Village, Mawasangka District, Central Buton Regency. The population concerned by this research is made up of seaweed producers and traders. The sampling method for farmers uses the simple random sampling method, while marketers use snowball sampling. The number of samples taken by farmers is 12 people, collectors are 3 people. The data collected comes in the form of marketing channels, sales volume, prices for each marketer, and marketing costs. The data is analyzed using qualitative descriptive data, marketing margins and marketing effectiveness. Based on the results of the study, the marketing channel in Napa Village, Mawasangka District, Central Buton Regency was efficient.